Ensemble deep learning for brain tumor detection - Alsubai, Shtwai; Khan, Habib Ullah; Alqahtani, Abdullah; Sha, Mohemmed; Abbas, Sidra; Mohammad, Uzma Ghulam (Frontiers in Computational Neuroscience, 2022)
With the quick evolution of medical technology, the era of big data in medicine is quickly approaching. The analysis and mining of these data significantly influence the prediction, monitoring, diagnosis, and treatment of tumor disorders. Since it has a wide range of traits, a low survival rate, and an aggressive nature, brain tumor is regarded as the deadliest and most devastating disease. Misdiagnosed brain tumors lead to inadequate medical treatment, reducing the patient's life chances. Brain tumor detection is highly challenging due to the capacity to distinguish between aberrant and normal tissues. Effective therapy and long-term survival are made possible for the patient by a correct diagnosis. Despite extensive research, there are still certain limitations in detecting brain tumors because of the unusual distribution pattern of the lesions. Finding a region with a small number of lesions can be difficult because small areas tend to look healthy. It directly reduces the classification accuracy, and extracting and choosing informative features is challenging. A significant role is played by automatically classifying early-stage brain tumors utilizing deep and machine learning approaches. This paper proposes the hybrid deep learning model Convolutional Neural Network-Long Short Term Memory (CNN-LSTM) for classification and predicting the brain tumor through Magnetic Resonance Images (MRI) images. The experiment is conducted on an MRI brain image dataset; data is preprocessed efficiently. Then, the Convolutional Neural Network (CNN) is applied to extract the significant features from MR images. The proposed model helps to predict the brain tumor with the significant classification accuracy of 99.1%, precision 98.8%, recall 98.9%, and F1-measure 99.0%.